Duration of Migraine Headaches in Children - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1999)
Children referred to the Headache Center at Children's Hospital Medical Center, Cincinnati, OH, Sept 1996-June 1997, were evaluated for clinical characteristics of the headaches, using criteria of the International Headache Society (IHS), and older criteria by Vahlquist and Prensky and Sommer for comparison.